MADURANISATION NATIVE GOVERNMENT BUREAUCRACY ELITE IN BESUKI RESIDENCY 1818-1942 (History Department, Semarang State University and Historian Society of Indonesia, 2018)
The purpose of this article is to discuss how the realization of maduranisation bureaucracy elite in Besuki Residency in 1818-1942. Maduranisation is a policy from the colonial government implicated by the elected candidate of regent. They are Madurese, although geographically, Besuki Resindence is located in East Java. This policy is implicated by argumentation and good political calculation. Besides, the elite communities in Madura are loyal to the Dutch government. They hope that they will have a good relation because the local governments execute the daily governance. On the other hand, the majority of government comes from Javanese. Consequently, the accumulation of power is failed because it is able to destroy the Dutch colonial government. Artikel ini ditulis dengan tujuan untuk membahas tentang bagimana pelaksanaan maduranisasi elite birokrasi di Karesidenan Besuki dari 1818-1942.Maduranisasi adalah sebuah kebijakan dari pemerintah kolonial yang dilaksanakan melalui pemilihan bupati dari etnis Madura walaupun secara geografis Karesidenan Besuki terletak di Jawa Timur. Kebijakan ini dilakukan berdasarkan argumentasi dan perhitungan politik yang baik bahwa elite Madura sangat loyal terhadap pemerintah Belanda. Pemerintah Belanda berharap di satu pihak bupati dari etnis Madura akan menjadi partner yang baik, sebaliknya di pihak lain Pemerintah Hindia Belanda bisa memotong alur/keturunan dari penguasa lama (Blambangan). Hasil dari kebijakan ini adalah, empat kabupaten di Karesidenan Besuki secara perlahan didominasi oleh elite Madura, terutama keturunan dari Pamekasan dan Sumenep, sementara keturunan dari penguasa Blambangan hanya memerintah sampai tahun 1889.